Hakikat Evaluasi (Pengertian Pengukuran, Penilaian, Evaluasi; Fungsi & Tujuan Penilaian, Ciri-Ciri Penilaian Pendidikan) - Ahsan Nadya; Disa Devia; Gusmaneli Gusmaneli (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Measurement, assessment and evaluation themselves have similarities, but in essence measurement, assessment and evaluation are quite different in terms of their application. In this article, we discuss the nature of evaluation (meaning measurement, assessment, evaluation; function & purpose of assessment, characteristics of educational assessment). The approach used is through a literature review, by collecting data from various scientific sources such as journals, scientific articles, books and other relevant information related to the topic. The data obtained was then analyzed qualitatively, and the results of the analysis were presented systematically and objectively by the author. It is concluded that measurement, assessment and evaluation have their respective roles in the world of education and are mutually binding, such as measurement in the world of education can be carried out with various tests which will later produce grades. From this score, the teacher will pay attention to whether the student should get additional help or not. And this is an evaluation in education.